Energy Balances and Electricity Profiles 2011 - United Nations (United Nations, 2014)
The 2011 Energy Balances and Electricity Profiles contains energy balances for about 125 developing countries, showing production, trade, conversion and consumption in energy units for all energy products; and electricity profiles for about 180 countries, providing detailed information on production, trade and consumption of electricity, net installed capacity and thermal power plant input for selected developing and developed countries.